Pengaruh Adversity Quotient dan Personal Attitude Terhadap Minat Berwirausaha Mahasiswa - Jean Elikal Marna; Dianita Dwi Putri (Jurnal Ecogen, 2023)
The aims of this research is to investigate the influence of Adversity Quotient and Personal Attitude on Entrepreneurship Interest in Economics Education students. This study's population consisted of 216 students enrolled in Economics Education at Padang State University's Faculty of Economics in 2018, 2019, 2020, and 2021. This study employed Proportionate Stratified Random Sampling as its sampling method. The data used are both primary and secondary. The data gathering tool used is a questionnaire. Descriptive analysis, analysis precondition test, multiple regression, T test, F test, and determinant coefficient were employed in data analysis. The sesult of this research is student's interest in entrepreneurship will be high if student has a positive view of what they are doing, this view will lead someone to be able to maintain or continue his interest in entrepreneurship.